Sustainable Development in the Russian Federation – Indicator-based Approach - Bartniczak, Bartosz; Raszkowski, Andrzej (Problemy Ekorozwoju, 2017)
The presented study discusses problems referring to the concept of sustainable development in the Russian Federation in the period 2004-2013. The first part presents, e.g. the importance of creativity, good space governance, the significance and reasons for sustainable development in Russia. Next, sustainable development indicators, selected for the analysis, are characterized in accordance with the approach to sustainable development level measurement adopted by the European Union. The synthetic measure of development (SMD) was applied as the research method, the data for calculations were collected from The World Bank resources. The research results presenting values of particular indicators in the studied years and the values of SMD constitute the core of the study. Despite relatively unfavourable or moderate results a gradual improvement of the situation was observed in the context of sustainable development concept implementation in Russia over the studied years.